Taxonomic study of the genus Cranionycta de Lattin, 1949 (Lepidoptera: Noctuidae: Acronictinae) with description of a new subgenus and 21 new species - Kiss, Ádám (Zootaxa, 2025)
The present paper contains the description of one new subgenus (Nefrendinycta subgen. nov.) and 21 new species: Cranionycta (Cranionycta) moganshanica sp. nov., C. (C.) aurata Kiss & Matov sp. nov., C. (C.) muscosa Kiss, Matov & Han sp. nov., Cranionycta (Nefrendinycta) lobophorus sp. nov., C. (N.) versicolor sp. nov., C. (N.) mailungana sp. nov., C. (N.) delattini sp. nov., C. (N.) warreni sp. nov., C. (N.) dierli sp. nov., C. (N.) senjelungma sp. nov., C. (N.) gorkhalii sp. nov., C. (N.) punctifera sp. nov., C. (N.) pallidobrunnea sp. nov., C. (N.) castanea Kiss & Han sp. nov., C. (N.) fuscothoracica sp. nov., C. (N.) boursini sp. nov., C. (N.) jubingica sp. nov., C. (N.) albothoracica sp. nov., C. (N.) dieteri sp. nov., C. (N.) atrazonaria sp. nov., C. (N.) falcata sp. nov.). One new combination is presented for Acronicta nigralbata Warren, 1914 as C. (N.) nigralbata (Warren, 1914) comb. nov. One species is reinstated from synonymy (C. (C.) inquieta (Draudt, 1950) stat. rev.) and one species is reduced to subspecies (C. (C.) oda transversa (Kozhanchikov, 1950) stat. rev.). Lectotypes are designated for Craniophora inquieta Draudt, 1950, Craniophora transversa Kozhanchikov, 1950 and Acronicta nigralbata Warren, 1914. Adult habitus and male and female terminal abdominal segments of most species are figured for the first time, with 146 figures in 18 plates.